Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan (MUSRENBANG) Tahun 2019 di Kabupaten Bondowoso Perspektif Undang-Undang Nomor 6 Tahun 2014 tentang Desa - Mohammad Wasil (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
The Development Planning Deliberation which has been regulated in the Minister of Home Affairs Regulation Number 66 of 2007. Furthermore, in Law Number 6 of 2014 Article 80 Paragraph 1 explains that village development planning as referred to by involving village communities, village development planning deliberations determine priorities, programs, activities, and village development needs funded by the village income and expenditure budget, village community self-help and or district / city regional income and expenditure budgets based on an assessment of community needs. In this study, there are two core questions, namely first, how is the participation of the people of Wonosari village, Grujugan sub-district, Bondowoso district in the Musrenbang Perspective of Law Number 6 of 2014 concerning Village Article 80? Second, what factors influence community participation in Musrembang in the village Wonosari? By using observation, interview, and documentation techniques, the results of this research can be obtained, namely: Law Number 14 concerning Villages, seen from Article 80 that Wonosari Village in implementing village Musrenbang, a.) Wonosari Village has implemented the Village Musrenbang as it should have been implemented once a year and held in January. b) Whereas community participation in the Musrenbang in Wonosari village is following regulations that include elements of the community. For all elements in the Law for representation from the community, two factors affect the participation of the Wonosari village community, namely internal and external factors.